2021
DOI: 10.1371/journal.pone.0249558
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatic analysis of the inhibin-betaglycan-endoglin/CD105 network reveals prognostic value in multiple solid tumors

Abstract: Inhibins and activins are dimeric ligands belonging to the TGFβ superfamily with emergent roles in cancer. Inhibins contain an α-subunit (INHA) and a β-subunit (either INHBA or INHBB), while activins are mainly homodimers of either βA (INHBA) or βB (INHBB) subunits. Inhibins are biomarkers in a subset of cancers and utilize the coreceptors betaglycan (TGFBR3) and endoglin (ENG) for physiological or pathological outcomes. Given the array of prior reports on inhibin, activin and the coreceptors in cancer, this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 143 publications
0
6
0
Order By: Relevance
“…While inhibin levels (inhibin A and B) cycle across the lifespan of healthy females and dramatically decrease at the onset of menopause 13 , elevated inhibinα levels are found in ovarian, gastric, hepatocellular, and prostate cancers 14 17 . Total inhibin protein levels comprising free inhibinα, inhibin A and inhibin B are also an established diagnostic marker alone and/or in combination with CA125, for ovarian cancers 18 and have been proposed as a potential tumor specific target for therapy 8 , 15 , 17 , 19 , 20 . Inhibinα levels are also predictive of survival in multiple cancer types with gene signatures that correlate with INHA expression, providing a highly accurate prognostic model for predicting patient outcomes 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While inhibin levels (inhibin A and B) cycle across the lifespan of healthy females and dramatically decrease at the onset of menopause 13 , elevated inhibinα levels are found in ovarian, gastric, hepatocellular, and prostate cancers 14 17 . Total inhibin protein levels comprising free inhibinα, inhibin A and inhibin B are also an established diagnostic marker alone and/or in combination with CA125, for ovarian cancers 18 and have been proposed as a potential tumor specific target for therapy 8 , 15 , 17 , 19 , 20 . Inhibinα levels are also predictive of survival in multiple cancer types with gene signatures that correlate with INHA expression, providing a highly accurate prognostic model for predicting patient outcomes 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Total inhibin protein levels comprising free inhibinα, inhibin A and inhibin B are also an established diagnostic marker alone and/or in combination with CA125, for ovarian cancers 18 and have been proposed as a potential tumor specific target for therapy 8 , 15 , 17 , 19 , 20 . Inhibinα levels are also predictive of survival in multiple cancer types with gene signatures that correlate with INHA expression, providing a highly accurate prognostic model for predicting patient outcomes 20 . However, the mechanism of inhibin expression in cancers have not been delineated.…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer cells, downregulation of INHBA can delay the growth of primary tumors, inhibit the migration of tumor cells, and reduce the possibility of lung metastasis [ 7 ]. At present, it has been found that there is differential expression of INHBA in cervical cancer tissues [ 8 ], but whether it is related to the response of cervical cancer immune cells is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic methods, including analysis of GBM microarray and high-throughput sequencing, are effective strategies for the exploration of therapeutic targets in GBM [6][7][8]. Weighted gene coexpression network analysis (WGCNA) is a potent tool for uncovering complex mechanisms and multigene analysis of high-throughput data, particularly for exploring the relationship between genes and traits of samples [9][10][11].…”
Section: Introductionmentioning
confidence: 99%